Dynamic response of viscoelastic multiple-core sandwich structures. (20th January 2021) - D'Ottavio, M.; Krasnobrizha, A.; Valot, E.; Polit, O.; Vescovini, R.; Dozio, L.
Highlights: Viscoelastic multi-core sandwich structures are investigated in the frequency domain Fractional Derivatives Zener model parameters are identified from other model data Numerical tool based on efficient variable-kinematics approach and Ritz solution Elementary reduced-order models are compared against the direct solution Transverse normal deformation of damping plies plays an important role Abstract: This work focuses on the free and forced vibrations of sandwich beams and plates hosting an arbitrary number of damping cores. A fractional derivatives Zener-type model is adopted for representing the frequency-dependent viscoelastic behaviour, along with conventional series developments. The structural models are formulated within an established variable kinematics approach, which enables to investigate the role of specific assumptions and to identify the most accurate model at a least number of degrees of freedom. Approximate solutions are found by a computationally efficient Ritz method that allows to take into account any type of boundary conditions. Modal loss factors and damped eigenfrequencies are obtained from a complex eigenvalue problem, for which a modal strain energy approach or a complex eigensolution can be employed. Frequency responses can be computed by a direct approach or by elementary modal projection algorithms. Results are reported for conventional and innovative sandwich configurations. Different modelling and solution strategies are compared and the role of transverse normal deformation of the mechanically weak viscoelastic plies is particularly emphasised.